Optimizing the Quality of Anti-Bullying Education Services in Islamic Boarding Schools - Baharun, Hasan; Sholihah, Imroatus; Imam, Ombra A. (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
Bullying is detrimental to students’ mental health, academic achievement, and character development, so Islamic boarding schools need to study it further. This study aims to improve anti-bullying education programs in Islamic boarding schools using Islamic ideals. Qualitative case study data were collected through observation, interviews, and comprehensive recording at Nurul Jadid Islamic Boarding School. This study highlights the need to integrate classmates and foster carers in building a bullying-free environment in Islamic boarding schools, as well as modifying internal norms and adding anti-bullying instructions to the curriculum. Peers serve as mediators in the Bullyguard technique, which has demonstrated efficacy in maintaining a secure environment and promoting amicable conflict resolution. Another option under consideration to enhance the quality of anti-bullying educational services is the Child-Friendly Islamic Boarding School Program. Focussing on the physical, mental, and social well-being of kids. The objective of this program is to cultivate an environment that promotes comprehensive student development. This study enhances the knowledge base concerning the quality of religious-based educational services and aids in the formulation of anti-bullying protocols in Islamic boarding schools. This research's findings facilitate additional investigation into the factors affecting educational success and promote the development of more comprehensive policies for higher education institutions.